Computer and information science - Lee, Roger (Studies in Computational Intelligence, 2013)
This edited book presents scientific results of the 12th IEEE/ACIS International Conference on Computer and Information Science (ICIS 2013) which was held on June 16-20, 2013 in Toki Messe, Niigata, Japan. The aim of this conference was to bring together scientists, engineers, computer users, and students to share their experiences and exchange new ideas, research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them The conference organizers selected the best 20 papers from those papers accepted for presentation at the conference. The papers were chosen based on review scores submitted by members of the program committee, and underwent further rigorous rounds of review.